Cotton Fabric Coating by rGO and Polymethylsiloxane Layer with Antibacterial, Hydrophobic and Photothermal Properties - Sakti, Lintang Kumoro; Sheha, Geometry Amal Nur; Radhiyah, Cut Putri Saba Miftah; Nugraha, Jakariya; Eddy, Diana Rakhmawaty; Permana, Muhamad Diki; Maksum, Iman Permana; Deawati, Yusi (Trends in Sciences, 2023)
The cotton fabric, which is widely used as personal protective equipment, is vulnerable to droplets that may contain pathogens. Thus, the functionalization of cotton fabric is usually carried out to get the desired properties. Graphene-based materials have some interesting properties like hydrophobic, photothermal, and antibacterial properties that can be used to modify cotton fabric. This research has made a cotton fabric coated with graphene from coconut shells and polymethyl siloxane. Graphite was obtained from burning coconut shells, and the modified Hummers method was used to get a graphene oxide solution (GO). A graphene oxide layer on cotton fabrics was added by the dip-pad-dry process, followed by reduction using ascorbic acid to produce a reduced graphene oxide (rGO) and immersion of cotton fabrics with methyl trichlorosilane in n-hexane to produce a polymethyl siloxane (PMS) layer. Scanning electron microscope (SEM) and Fourier-transform infrared (FTIR) are used to determine the morphology and functional groups in rGO-PMS-coated cotton fabric. Contact angle measurements to determine the hydrophobicity of the rGO-PMS-coated cotton fabric, which exhibits hydrophobic properties with a contact angle of 146.3 °, which can show self-cleaning ability while preventing water droplets from entering the fabric. Antibacterial activity was carried out using the disc diffusion method against Staphylococcus aureus and delivered a good result. The rGO-PMS-coated cotton fabric also shows photothermal capability when irradiated with infrared lamps. HIGHLIGHTS Graphene is a material that has various properties that can be exploited for the functionalization of ready-to-use materials Waste derived from natural resources can be used as a source of graphene, which can reduce the cost of graphene production Cotton fabric as a functionalized material can adopt the combined properties of graphene and silane such as photothermal, antibacterial, and hydrophobic properties GRAPHICAL ABSTRACT